Purchasing Vegetables in the Digital Era: A Systematic Literature Review on Online Buying Behavior in E-Commerce - Soeyatno, Rahmah Farahdita; Darjanto, Arief; Syaukat, Yusman; Nurmalina, Rita (Universitas Panji Sakti, 2023)
This study aims to examine and analyze consumer behavior in purchasing vegetables online through E-Commerce in Indonesia. This can contribute to the creation of online food product marketing in Indonesia. A systematic literature review (SLR) was conducted based on studies of purchasing vegetables online through E-Commerce. The data collection method used the Population, Intervention, Comparison, and Outcome (PICO) framework. The selected articles were relevant to the research objectives (with keywords